Association Between Vitamin D Deficiency and Recurrent Tonsillitis - Shrestha, Diva; Bista, Meera (Journal of Nepal Health Research Council, 2023)
Background: Tonsillitis is defined as an inflammation of the tonsils characterized by signs of tonsillar erythema and exudates and recurrent tonsillitis is at least 7 episodes of acute tonsillitis in a year, or a minimum of 5 episodes in a year for 2 consecutive years, or at least 3 episodes in a year for 3 consecutive years. There are many research that have hypothesized the association of low level of Vitamin D and recurrent attacks of acute tonsillitis. Methods: A single centre prospective, cross sectional analytical study was conducted from 2021 June to 2022 March in Department of ENT and Head and Neck surgery in Kathmandu Medical College Teaching Hospital. The study participants were recruited from ENT Head and Neck OPD and the data on number of episodes of recurrent attacks of tonsillitis and serum level of Vitamin D were collected. Results: 78.8% of patients with tonsillitis had low level of serum Vitamin D (less than 30ng/ml) and 21.2% had optimal level of serum Vitamin D (more than 30ng/ml). The incidence of recurrent tonsillitis was 40.9% in patients with low level of Vitamin D where as the incidence of recurrent tonsillitis was 18.1% in patients with optimal level of Vitamin D. Conclusions: The low serum level of Vitamin D was found to be associated with recurrent episodes of tonsillitis.Keywords: Recurrent tonsillitis; vitamin D.